Analisis Pemborosan di Poli Rawat Jalan Unit Fisioterapi Rumah Sakit Swasta Menggunakan Pendekatan Lean Service - Purba, Simon B Saitama; Sumiati, Sumiati (BRILIANT: Jurnal Riset dan Konseptual, 2025)
A hospital is a health service that carries out health efforts and improves public health. One of the private hospitals located in Surabaya already has full accreditation. However, in reality, the implementation of health services in this private hospital is often faced with various challenges, namely the length of waiting time, lack of therapy personnel and physiotherapy service facilities, and lack of service information provided by nurses which causes some waste. Based on the above problems, the lean service method is used to reduce waste in the process of providing physiotherapy services. Identification of waste is done using the Value Stream Mapping method. Activity mapping will be done by Process Activity Mapping method and to find out the critical waste will be done by questionnaire processing. The results obtained are critical waste or the most common are waiting and duplication. After being given a proposal for improvement, the lead time which was originally 6883 seconds can decrease to 4409 seconds. It is hoped that this research can improve the efficiency and effectiveness of the physiotherapy service process at the Private Hospital.